Robustness analysis of the entropic regularization parameter in the Gromov–Wasserstein alignment step of TransMarker. - Fatemeh Keikha (20917848) (2025)
(A) Classification performance (ACC, AUROC, and AUPRC) across . (B) Spearman rank correlation of gene prioritizations relative to the default . (C) Mean rank deviation of the top 20 biomarkers across ε values. (EPS)